Salvaging a cultural identity through reintegration - Marta Gomez Ubierna (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The following article owes much to the master’s thesis on “The Restoration of the pulpit in the church of San Leonardo in Arcetri”, which deals with an outstanding work of Florentine Romanesque art. The remaining architectural elements of the pulpit, dismantled in the sixteenth century, were reassembled on a number of occasions in 1782 and 1921, as a result of efforts to reclaim the cultural identity of the region through a revival of its medieval heritage, even down to its most fragmentary remains. The main difficulty encountered during these interventions - such as the restoration work carried out by the “Opificio delle Pietre Dure” in 2009 - lay in the recovery of the black and white polychromy, of the quintessentially Florentine marble inlay through various interventions involving the integration of the stone. Study of the techniques and materials used has provided a unique opportunity to map out the various stages of restoration that the piece underwent, identifying the materials used in each intervention, allowing choices to be made regarding the conservation methods. The aim of the current project was the integration of new, completely reversible and compatible elements into the polychromatic marble inlay, elements that were created on the basis of the results of an experiment  with synthetic materials and their various methods of application.